Combined responses of primary coral polyps and their algal endosymbionts to decreasing seawater pH ... - Scucchia, Federica; Malik, Assaf; Zaslansky, Paul; Putnam, Hollie; Mass, Tali (Dryad, 2021)
With coral reefs declining globally, resilience of these ecosystems hinges on successful coral recruitment. However, knowledge of the acclimatory and/or adaptive potential in response to environmental challenges such as ocean acidification (OA) in earliest life stages is limited. Our combination of physiological measurements, microscopy, computed tomography techniques and gene expression analysis allowed us to thoroughly elucidate the mechanisms underlying the response of early life stages of corals, together with their algal partners, to the projected decline in oceanic pH. We observed extensive physiological, morphological and transcriptional changes in surviving recruits, and the transition to a less-skeleton/more-tissue phenotype. We found that decreased pH conditions stimulate photosynthesis and endosymbiont growth, and gene expression potentially linked to photosynthates translocation. Our unique holistic study discloses the previously unseen intricate net of interacting mechanisms that regulate the ... : The readme file contains an explanation of each variable in the dataset. Information on how the measurements were done can be found in the associated manuscript referenced above. ...